Adubação com enxofre na cultura da cebola - Lacerda, Rodolfo Rodrigo de Almeida (2021)
Sulfur (S) contributes to the growth, productivity and quality of the onion. Responsible for the regulation, assimilation and synthesis of amino acids necessary for the production of proteins, S is the third or fourth in decrease order of onions‟ accumulation. In Brazil, the sources of S are associated with mixtures of fertilizers with high concentration of NPK, which do not meet the demand for S by the onion, affecting the productivity of the crop. Therefore, the objective was to evaluate the productivity, economic viability and quality of the onion, fertilized with doses of S under field conditions in the Brazilian semiarid region. Two experiments were carried out in Mossoró, RN, from June to November 2018 and from June to November 2019. The experimental design was in randomized blocks in a 2 x 7 factorial scheme, with 14 treatments and four replications. The evaluated factors were cultivars (Rio das Antas and IPA 11) and S doses (0; 10; 20; 30; 40; 50 and 60 kg ha-1). The application of 30 to 40 ha-1 of S provided greater productivity in Rio das Antas and maximized net revenue, favoring an increase in the percentage of larger bulbs (boxes 3 and 4) and a reduction in smaller bulbs. For the cultivar IPA 11, the highest rate of return was observed when applying 10 kg ha-1 of S, with return of R$4.4 for every real invested. The fertilization with S contributed to the higher content and accumulation of the nutrient in the bulb of both cultivars up to 30 kg ha-1, improving the quality of the bulbs. The S contributed to the increase of firmness, titratable acidity and soluble solids of the bulbs of the cultivar IPA 11, and the reduction of the SS / AT of the cultivar Rio das Antas. The cultivar IPA 11 fertilized with 60 kg ha-1 of S produced bulbs with "very strong" pungency